144k views
1 vote
What is the inverse of the function below?

f(x) = x/3 -2
O A. f1(x) = 2(x+3)
O B. f¹(x) = 3(x+2)
O c. f¹(x) = 3(x - 2)
OD. f¹(x) = 2(x-3)

1 Answer

3 votes

Answer:

f⁻¹
(x) =
3(x+2)

Explanation:

The first step to finding the inverse of a function is to let
y=f(x).

This would mean
y=(x)/(3)-2.

Then we swap
x and
y in the formula.


x = (y)/(3) -2

Then rearrange for
y:


x=(y)/(3)-2 \\\\x+2=(y)/(3)\\\\3(x+2)=y

This new equation of
y is the inverse function.

f⁻¹
(x) =
3(x+2)

User Dsign
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.